Thiol-capped gold: from planar to irregular surfaces - Vericat, Carolina (2008)
Thiol-capped metals, in particular gold, have a wide range of technological applications, especially for building systems by bottom-up methods. In most cases, stability of the organic film during exposure to ambient conditions and/or to electrolyte solutions is a crucial requirement. In this work we discuss the stability of butanethiol self-assembled monolayers (SAMs) on planar, nanocurved and irregular Au surfaces against both air exposure and electrodesorption in aqueous media. We have found a slower rate of air oxidation and increased stability against electrodesorption for butanethiol monolayers on highly irregular Au surfaces as compared to those on planar surfaces. The increased stability of SAMs on highly irregular surfaces is promising because desorption and degradation seriously limit their application in nanotechnology.